The Role Of The Indonesian Automatic Finger Print Identification System (Inafis) In Identifyng Perpetrators Of Murder Cases (A Cases Study In The Regional Police Of West Sumatera) - Yoga Pratama Pratama; Deaf Wahyuni Ramadhani (Universitas PGRI Madiun, 2021)
Indonesia Automatic Finger Print Identification System (Inafis) is a unit that plays a role in identifying a person through scientific means, by examining fingerprints at a crime scene. As stipulated in Article 15 paragraph (1), Law Number 2 of 2002 concerning the Indonesian National Police states that,